PERAN GURU BK DALAM MENGEMBANGKAN EQ MELALUI LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN SOLUTION FOCUSED BRIEF COUNSELING (SFBC) DI SMA NEGERI 1 JOGOROGO TAHUN PELAJARAN 2025/2026 - Danela Arma Nissa; Hera Heru Sri Suryanti; Ahmad Jawandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students' emotional intelligence (EQ) plays an important role in supporting their academic achievement, social relationships, and personal development. However, many students still experience difficulties in recognizing, managing, and expressing their emotions effectively. This study aimed to determine the role of Guidance and Counseling teachers in developing students' emotional intelligence through group counseling services using the Solution Focused Brief Counseling (SFBC) approach at SMA Negeri 1 Jogorogo in the 2025/2026 academic year. This study employed a qualitative descriptive research design. The research subjects consisted of the Guidance and Counseling teacher and students who participated in the group counseling sessions. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation. The findings revealed that the Guidance and Counseling teacher performed significant roles as a facilitator, motivator, and guide in enhancing students' emotional intelligence through SFBC-based group counseling. The teacher encouraged students to identify their strengths, explore solutions through solution-focused questioning, and develop confidence in resolving their own problems. The implementation of group counseling resulted in improvements in students' self-awareness, emotional regulation, self-motivation, empathy, and social skills. Overall, the SFBC approach proved to be effective in supporting the development of students' emotional intelligence and fostering more positive emotional and social behavior.